CROSS-CULTURAL ADAPTATION AND VALIDATION OF THE MONTREAL CHILDREN'S HOSPITAL FEEDING SCALE INTO BRAZILIAN PORTUGUESE - Patricia Barcellos Diniz; Simone Chaves Fagondes; Maria Ramsay (Sociedade de Pediatria de São Paulo, 2021)
ABSTRACT Objective: To cross-culturally adapt and validate the Montreal Children's Hospital Feeding Scale (MCH-FS) into Brazilian Portuguese. Methods: The MCH-FS, originally validated in Canada, was validated in Brazil as Escala Brasileira de Alimentação Infantil (EBAI) and developed according to the following steps: translation, production of the Brazilian Portuguese version, testing of the original and the Brazilian Portuguese versions, back-translation, analysis by experts and by the developer of the original questionnaire, and application of the final version. The EBAI was applied to 242 parents/caregivers responsible for feeding children from 6 months to 6 years and 11 months of age between February and May 2018, with 174 subjects in the control group and 68 ones in the case group. The psychometric properties evaluated were validity and reliability. Results: In the case group, 79% of children were reported to have feeding difficulties, against 13% in the control group. The EBAI had good internal consistency (Cronbach's alpha=0.79). Using the suggested cutoff point of 45, the raw score discriminated between cases and controls with a sensitivity of 79.4% and specificity of 86.8% (area under the ROC curve=0.87). Conclusions: The results obtained in the validation process of the EBAI demonstrate that the questionnaire has adequate psychometric properties and, thus, can be used to identify feeding difficulties in Brazilian children from 6 months to 6 years and 11 months of age.